The Global Economic Crisis through the prism of the Great Depression - Jovan Đurašković (Management, 2014)
This paper presents the main aspects of the 2008 global economic crisis through the prism of the Great Depression of the 1930s. The aim of this paper is to illustrate the importance of the lessons learned in the Great Depression in overcoming the modern global economy disorders by analyzing the causes of the crisis and the response from the US economic policy. The methods employed in the paper are the following: the method of analysis, the comparative method and the method of deduction. An analytical review of the US anti-crisis economic policy based on relevant statistical data has been presented. The survey results clearly indicate that the crisis has led to a sudden reaffirmation of Keynesian economic policies. The monetary policy was extremely expansionary. The Fed cut its key interest rates to a record low and through open market operations significantly expanded its assets. Confidence in the banking system was preserved and the risk of deflation avoided. The fiscal policy was also counter-cyclical and a few fiscal stimulus packages confirmed a commitment to a strategy of stimulating aggregate demand. By selecting a coordinated and synchronized intervention policy through the G20, the mistakes of economic policy makers of the Great Depression were avoided and pre-conditions created for a structural reform on financial market and economic policy. Keywords: global economic crisis, the Great Depression, financial system, financial regulation, counter-cyclical economic policy, the USA.